Current state and perspectives of the aquacultural production of Silurians in Europe - (:unkn) unknown (My University, 1994)
The silurian aquacultural production in Europe concerns the indigenous European catfish (silurus glanis) and other species recently introduced such as the African catfish or the American catfish. Only a small production is concerned, especially in Germany, France, Italy, Hungaria, the Czech Republic and the Netherlands.
Keywords: African Research